EFEKTIFITAS SARI BUAH PEPAYA MENGKAL TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS DELI TUA KAB. DELI SERDANG - Hariati, Hariati; GINTING, SULASTRI (Jurnal Kajian Kesehatan Masyarakat, 2020)
Background: Blood pressure is the combined pressure from pumping by the heart, resistance from the walls of the arteries, and heart valve covers. Aimed: This study aims to explain the effect of blood pressure on blood pressure in hypertensive patients. Method: This research method uses quantitative design with field experimental methods with one group pretest-posttest design approach. Subjects were hypertensive patients. A total of 12 subjects were selected using the purposive sampling method. Data collection techniques by filling out observations. Result: The results showed that the average blood pressure of systole before administration of papal extract (Carica Papya) was 182.50 and after administration of papal extract (Carica papaya) was 142.50. It is also known that the average blood pressure of diastole before administration of papal extract (Carica Papaya) is 113.33 and after administration of papal extract mengkal (Carica Papaya) is 92.50.Conclusion: The importance of the application of papaya utilization in the community to lower blood pressure in order to improve the public health status